Care coordination for older people: an exploratory framework. (14th September 2015) - Hughes, Jane; Chester, Helen; Sutcliffe, Caroline; Xie, Chengqiu; Challis, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a framework for examining variation in care coordination arrangements for older people. Design/methodology/approach – A multi-method approach was adopted combining analysis of secondary data and primary data. There were two stages: the development of the framework and its constituent attributes and indicators; and its validation from two perspectives: a meeting with managers and focus groups with practitioners. It was informed by an existing generic framework; subsequent policy guidance; data from an English national survey; previous research; and international literature. Findings – The framework comprises 19 attributes each with indicators measuring performance relating to: organisational arrangements influencing service delivery; the performance of core tasks of care coordination; and differentiation within the process to distinguish between responses to different levels of need. Originality/value – Care coordination arrangements in England are characterised by diversity. This paper provides a framework for evaluating local arrangements thereby highlighting strengths and where improvements are needed. It offers a means to promote programme fidelity. As such it has utility for both service commissioners and providers.